Penerapan Prinsip Deklarasi Rio: Strategi Mengatasi Perubahan Iklim - Devi Ratu Ng. D. Wulla; Muhammad Sarjan (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
Climate change is a global challenge that requires a collective and coordinated response from the international community. In an effort to overcome the impact of climate change on the balance of natural resources and the environment, the principles contained in the Rio Declaration on Environment and Development can be an important basis. This paper explains the application of the principles of the Rio Declaration in overcoming climate change, such as the Principle of Common Concern of Humankind, the Principle of Common but Differentiated Responsibility, the Principle of Sustainable Development and the Principle of Public Participation. By applying these principles, we can create better and more sustainable solutions to the challenge of climate change and provide long-term environmental, social and economic benefits.